2023
DOI: 10.1093/ofid/ofad034
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Cefepime vs Carbapenems for Bacteremia Caused by Enterobacterales With Moderate to High Risk of Clinically Significant AmpC β-lactamase Production

Abstract: Background Limited data suggest that serious infections caused by Enterobacterales with a moderate to high risk of clinically significant AmpC production can be successfully treated with cefepime if the cefepime minimum inhibitory concentration (MIC) is ≤2 µg/mL. However, isolates with a cefepime susceptible dose-dependent (SDD) MIC of 4-8 µg/mL should receive a carbapenem due to target attainment and extended-spectrum β-lactamase (ESBL) concerns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…The median (IQR) duration of EI-BL therapy was 4 (3-9) days. The median (IQR) duration of antibiotic therapy in the PSM cohort was 11 (9)(10)(11)(12)(13)(14) days, similar between both treatment groups.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The median (IQR) duration of EI-BL therapy was 4 (3-9) days. The median (IQR) duration of antibiotic therapy in the PSM cohort was 11 (9)(10)(11)(12)(13)(14) days, similar between both treatment groups.…”
Section: Resultsmentioning
confidence: 87%
“… 1 , 2 , 3 , 4 Pharmacokinetic and pharmacodynamic studies indicate that extending the infusion of a β-lactam agent may be particularly beneficial for gram-negative organisms with elevated antibiotic MICs. 1 Several observational studies 5 , 6 , 7 , 8 , 9 , 10 , 11 and clinical trials 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 have investigated the effect of EI-BL therapy on patient outcomes. Clinical trials, however, have shown conflicting results with some suggesting no benefit 12 , 13 , 14 , 17 , 18 , 20 , 21 and others indicating improved patient outcomes 11 , 15 , 16 , 19 with EI-BL therapy.…”
Section: Introductionmentioning
confidence: 99%